RASIO ESOTERIS AYAT-AYAT EKOLOGI: STUDI INTERPRETASI KITAB “RUH Al-MA’ANI FI TAFSIR Al-QUR’ANAL-ADZIM” KARYA IMAM AL-ALUSI - Fachri, Muhammad Saddam; Saka Arjuna, Bintang (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2024)
This research aims to examine the esoteric dimensions of ecological verses in the interpretation of Ruh al-ma'ani fi tafsiril Al-Qur'an al-azhim wa as-sab'il matsani by Imam Al-Alusi. This tafsir is known for its in-depth approach to the inner meaning of the Koran, including aspects of inner interpretation in ecological verses that are neglected in other research. This research uses a qualitative method with a library research type of research which uses library data sources as a reference. This research is descriptive analytical in nature to explore how al-Alusi interprets verses relating to the environment and the universe. The research findings try to show that Imam Al-Alusi not only discusses the zahir (exoteric) meaning of ecological verses, but also explores the inner (esoteric) meaning which includes the spiritual relationship between humans and nature, human moral responsibility in preserving the environment, as well as the role of nature as signs of God's greatness. This research highlights the relevance of esoteric interpretation in facing contemporary ecological challenges and invites readers to reflect on the deep meaning of Al-Quran verses related to ecology.